Revisiting Interest Rate – Exchange Rate Dynamics in South Africa: How Relevant is Pandemic Uncertainties? - Percy Mkhosi; Ismail Fasanya (Scientific Annals of Economics and Business, 2022)
This paper revisits the link between exchange rate and interest rate considering the role of uncertainty due to infectious diseases in the South African economy using monthly data from January 1985 to August 2020 within a nonparametric framework. First, we examine the relationship between the exchange-interest rates hypothesis and observe a significant positive link, especially during the pandemic. Second, we analyze the volatility spillover among exchange rates, interest rates and other macroeconomic fundamentals and find a strong connection with the interest rate being net receivers of shocks. Third, with evidence of nonlinearity in the variables, the nonparametric quantiles-based causality test shows that the spillover for each asset is driven by pandemic uncertainty around the median quantiles. Conclusively, this suggests that the role of global health news in influencing the South African financial cycle which consequently leads to capital flows and movements in the prices of assets across financial markets cannot be downplayed. Relevant policy implications can be drawn from these findings.